"Beards, Sandals, and Other Signs of Rugged Individualism": Masculine Culture within the Computing Professions. - Ensmenger, Nathan (Osiris, 2015)
Over the course of the 1960s and 1970s, male computer experts were able to successfully transform the "routine and mechanical" (and therefore feminized) activity of computer programming into a highly valued, well-paying, and professionally respectable discipline. They did so by constructing for themselves a distinctively masculine identity in which individual artistic genius, personal eccentricity, anti-authoritarian behavior, and a characteristic "dislike of activities involving human interaction" were mobilized as sources of personal and professional authority. This article explores the history of masculine culture and practices in computer programming, with a particular focus on the role of university computer centers as key sites of cultural formation and dissemination.